The impact of community expectations on corporate community involvement disclosures in the UK - Yekini, Kemi C.; Adelopo, Ismail; Adegbite, Emmanuel (Elsevier, 2017)
Despite increase mistrust between corporations and societies in the aftermath of the global corporate misbehaviours, the literature examining the impact of community concerns on corporate communications is undeveloped. Our paper is timely; it contributes to the literature on corporate social responsibility (CSR) by considering the impacts of community expectations on Corporate Community Involvement Disclosures (CCID) using a ten-year panel study. We advance CSR communication research by providing a fresh theoretical perspective – media-agenda-setting theory – to the broad CSR debate and the CCID subset of this debate. Our findings support the media-agenda theoretical expectation and provide important practice and policy recommendations for improving interactions between corporations and their communities.